Striatal Tyrosine Hydroxylase Is Stimulated via TAAR1 by 3-Iodothyronamine, But Not by Tyramine or β-Phenylethylamine - Zhang, Xiaoqun; Mantas, Ioannis; Alvarsson, Alexandra; Yoshitake, Takashi; Shariatgorji, Mohammadreza; Pereira, Marcela; Nilsson, Anna; Kehr, Jan; Andrén, Per E.; Millan, Mark J.; Chergui, Karima; Svenningsson, Per (Frontiers in Pharmacology, 2018)
The trace amine-associated receptor 1 (TAAR1) is expressed by dopaminergic neurons, but the precise influence of trace amines upon their functional activity remains to be fully characterised. Here, we examined the regulation of tyrosine hydroxylase (TH) by tyramine and beta-phenylethylamine (β–PEA) and compared to 3-iodothyronamine (T1AM). Immunoblotting and amperometry were performed in dorsal striatal slices from wild-type (WT) and TAAR1 knockout (KO) mice. T1AM increased TH phosphorylation at both Ser19 and Ser40, actions that should promote functional activity of TH. Indeed, HPLC data revealed higher rates of L-dihydroxyphenylalanine (DOPA) accumulation in WT animals treated with T1AM after the administration of a DOPA decarboxylase inhibitor. These effects were abolished both in TAAR1 KO mice and by the TAAR1 antagonist, EPPTB. Further, they were specific inasmuch as Ser845 phosphorylation of the postsynaptic GluA1 AMPAR subunit was unaffected. The effects of T1AM on TH phosphorylation at both Ser19 (CamKII-targetted), and Ser40 (PKA-phosphorylated) were inhibited by KN-92 and H-89, inhibitors of CamKII and PKA respectively. Conversely, there was no effect of an EPAC analogue, 8-CPT-2Me-cAMP, on TH phosphorylation. In line with these data, T1AM increased evoked striatal dopamine release in TAAR1 WT mice, an action blunted in TAAR1 KO mice and by EPPTB. Mass spectrometry imaging revealed no endogenous T1AM in the brain, but detected T1AM in several brain areas upon systemic administration in both WT and TAAR1 KO mice. In contrast to T1AM, tyramine decreased the phosphorylation of Ser40-TH, while increasing Ser845-GluA1 phosphorylation, actions that were not blocked in TAAR1 KO mice. Likewise, β-PEA reduced Ser40-TH and tended to promote Ser845-GluA1 phosphorylation. The D1 receptor antagonist SCH23390 blocked tyramine-induced Ser845-GluA1 phosphorylation, but had no effect on tyramine- or β-PEA-induced Ser40-TH phosphorylation. In conclusion, by intracellular cascades involving CaMKII and PKA, T1AM, but not tyramine and β-PEA, acts via TAAR1 to promote the phosphorylation and functional activity of TH in the dorsal striatum, supporting a modulatory influence on dopamine transmission.